Long-Term Azithromycin Reduces Haemophilus influenzae and Increases Antibiotic Resistance in Severe Asthma - Taylor, S.L.; Leong, L.E.X.; Mobegi, Fredrick; Choo, J.M.; Wesselingh, S.; Yang, I.A.; Upham, J.W.; Reynolds, P.N.; Hodge, S.; James, A.L.; Jenkins, C.; Peters, M.J.; et al. (AMER THORACIC SOC, 2019)
Copyright © 2019 by the American Thoracic Society